Recipients Perception of Blood Transfusion Risk in Some Selected Tertiary Care Hospitals (Anwer Khan Modern Medical College Journal, 2014)
This was a descriptive study carried out in the Medicine, Surgery, Gynae and Orthopedics ward of three randomly selected tertiary care hospitals at Dhaka, Bogra and Rangpur. It was aimed to evaluate the extent of understanding about the risk of blood transfusion among the blood recipients, to identify the common indications for blood transfusion through record review, to determine the recipients knowledge about indications of blood transfusion, their level of understanding about blood group, blood donors, and risk of blood transfusion and to find out the socio-demographic condition of recipients admitted at tertiary care hospitals. It was found that most of the respondents 63.17% were in the age group of 15-39 years and 56.95% were between primary to secondary level of education. More than half 56.83% respondents were housewife. The idea about indications of blood transfusion was found among 60.37% respondents. The idea about own blood group was found among 73.54% respondents. However, 52.93% respondents were unaware about the persons who can donate blood. Professional blood donor were the choice for own to only 15.60% respondents. The study also identified 57.32% respondents having risk of blood transmissible diseases. The respondents idea about transmissible diseases were identified as AIDs, Hepatitis-B, Syphilis and Malaria by 90.48%, 42.38%, 5.25% and 5.25% respectively. The study demands awareness and motivational program among younger and adult females in regards to transfusion transmissible diseases and its prevention. The importance of knowing blood group,donor selection and adverse effects of transfusion may also considered as a part of awareness program. It also demands a large scale community based survey to generate information towards development of effective strategy in minimizing risk of transfusion transmissible diseases in particular. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21129 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 30-33